UMP seals collaboration with universities from Indonesia - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 21 March 2023 - Universiti Malaysia Pahang (UMP) signed a memorandum of understanding (MoU) with Universitas Pembangunan Panca Budi, Medan and Universitas Katolik Santo Thomas, Medan in an effort to broaden collaboration in academia, research and internationalisation.